Solar Cells: Trade‐Offs in Thin Film Solar Cells with Layered Chalcostibite Photovoltaic Absorbers (Adv. Energy Mater. 11/2017). Issue 11 (7th June 2017) - Welch, Adam W.; Baranowski, Lauryn L.; Peng, Haowei; Hempel, Hannes; Eichberger, Rainer; Unold, Thomas; Lany, Stephan; Wolden, Colin; Zakutayev, Andriy
Abstract : In article number1601935, Andriy Zakutayev and co‐workers study trade‐offs in thin film solar cells with layered photovoltaic absorbers. Using high‐throughput combinatorial experimental methods, electron collection in such photovoltaic devices is found to be enhanced by a drift in the electric field, which however also reduces the solar cell voltage.